Determination of Storage (Starch/Glycogen) and Total Saccharides Content in Algae and Cyanobacteria by a Phenol-Sulfuric Acid Method - Zavřel, Tomáš; Očenášová, Petra; Sinetova, Maria A; Červený, Jan (Bio-protocol, 2018)
This is a protocol for quantitative determination of storage and total carbohydrates in algae and cyanobacteria. The protocol is simple, fast and sensitive and it requires only few standard chemicals. Great advantage of this protocol is that both storage and total saccharides can be determined in the cellular pellets that were already used for chlorophyll and carotenoids quantification. Since it is recommended to perform the pigments measurement in triplicates, each pigment analysis can generate samples for both total saccharide and glycogen/starch content quantification. The protocol was applied for quantification of both storage and total carbohydrates in cyanobacteria Synechocystis sp. PCC 6803, Cyanothece sp. ATCC 51142 and Cyanobacterium sp. IPPAS B-1200. It was also applied for estimation of storage polysaccharides in Galdieria (IPPAS P-500, IPPAS P-507, IPPAS P-508, IPPAS P-513), Cyanidium caldarium IPPAS P-510, in green algae Chlorella sp. IPPAS C-1 and C-1210, Parachlorella kessleri IPPAS C-9, Nannochloris sp. C-1509, Coelastrella sp. IPPAS H-626, Haematococcus sp. IPPAS H-629 and H-239, and in Eustigmatos sp. IPPAS H-242 and IPPAS C-70.
Keywords: Sugars; Chlorella; Synechocystis; Haematococcus; Colorimetry; Polysaccharides; Spectrophotometry; Carbohydrates